Simvastatin Induces Delayed Apoptosis Through Disruption of Glycolysis and Mitochondrial Impairment in Neuroblastoma Cells. Issue 3 (6th February 2020) - Kuzyk, Crystal L.; Anderson, Colin C.; Roede, James R.
Abstract : Simvastatin, a commonly used cholesterol‐lowering drug, inhibits the mevalonate pathway involved in the synthesis of the mitochondrial electron carrier coenzyme Q10 (CoQ10), as well as other bioenergetics substrates. The purpose of this study was to investigate simvastatin exposure on mitochondrial respiration, metabolic fuel preferences, and glucose utilization. We hypothesized that simvastatin at a noncytotoxic dose will impair energy metabolism in human neuroblastoma cells. SK‐N‐AS cells were exposed at acute and chronic time points and evaluated in a Seahorse XF analyzer, revealing decreased mitochondrial and glycolytic parameters. Flow cytometry showed a significant induction of apoptosis in simvastatin‐treated cells at 48 hours. Finally, multiple techniques were used to show that simvastatin‐mediated impairment of bioenergetics is more complex than CoQ10 depletion or hampered glucose uptake. Therefore, the data reported here represent a biphasic hit to mitochondria followed by reduction in glucose and glutamine metabolism in neuroblastoma; adding mechanism to potential pleotropic effects of statins.